Pengaruh Sustainability Report, Jumlah Rapat Komite Audit, Likuiditas, Leverage, dan Total Perputaran Aset terhadap Profitabilitas di Sektor Pertambangan - Rahmadani, Nabila; Yulazri (Universitas Sains dan Teknologi Komputer, 2025)
This study aims to analyze the effect of sustainability report disclosure, audit committee meeting frequency, liquidity, leverage, and total asset turnover on profitability in mining companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. Profitability is measured using Return on Equity (ROE). This research adopts a quantitative approach using secondary data obtained from annual financial statements and sustainability reports. The sample was selected using purposive sampling, yielding 34 mining companies with 102 observations in total. Multiple linear regression analysis was employed after fulfilling classical assumption tests. The results indicate that sustainability report disclosure, audit committee meetings, liquidity, leverage, and total asset turnover simultaneously have a significant effect on profitability. However, partially, total asset turnover has a positive and significant impact on profitability. Meanwhile, sustainability report disclosure, audit committee meeting frequency, liquidity, and leverage do not significantly affect profitability. These findings suggest that asset utilization efficiency plays a crucial role in improving profitability in the mining sector. This study is expected to provide insights for companies, investors, and regulators to understand the determinants of profitability better and to support improved corporate governance and financial decision-making in mining companies.